Дослідження методів оцінки і прогнозування ефективності іт проектів - Посипайко, О. В. (ХНУРЕ, 2023)
The presented paper aims to explore various methods for evaluating and predicting the effectiveness of IT projects. IT projects have become increasingly complex, making their evaluation and prediction challenging. This research focuses on identifying and analyzing the existing methods for evaluating IT project effectiveness and proposing new methods that can enhance accuracy and reliability. The paper analyzes various models such as ROI, Earned Value, and SWOT analysis and explores their limitations. The proposed research will help project managers and stakeholders in the IT industry to select the most effective methods for evaluating and predicting IT project effectiveness.